Моделювання професійно-орієнтованого ситуаційного навчання як педагогічна умова формування іншомовної професійної компетентності майбутніх дизайнерів середовища - Шайнер Ганна; Shayner Hanna (Видавництво «Код», 2025)
Abstract. The article is devoted to the problem of the formation of foreign language professional competence of future Environmental Designers. The article aims to analyse the modelling of professionally oriented situated learning as a pedagogical condition for forming foreign language professional competence of future Environmental Designers. Based on various factors which determine the typical functional responsibilities has been determined (development of the design concept of the object; execution of form formation, layout and modelling of design objects; implementation of compositional construction of design objects; ensuring the colour solution of the future design object; development and demonstration of visual presentations of the future design object; selection of materials taking into account their functional and aesthetic properties; monitoring the progress of work on the implementation of the design object project, etc.) which serves the grounds for effective modelling of professionally oriented situated learning. It is proved that modelling professionally oriented situated learning in the process of learning a foreign language of future Environmental Designers as an important condition for the formation of their foreign language professional competence is embodied within the framework of our study in a system of various situational tasks. In particular, we consider exercises for individual and collective solving of a wide range of problems in the field of conceptualisation, composition, stylisation, form and colour creation, material provision of design objects of various functional purposes with the preparation of means of visualisation and verbal presentation in a foreign language, and situational tasks of a clearly expressed communicative nature for practicing the norms of foreign language communicative behaviour through imitation of professional interaction with a client, employer, colleague, specialist in related industries, supplier of materials, etc. Modelled professionally oriented situated learning with integrated interactive elements are systematised by the degree of complexity and the presence or absence of supports within the «English for Designers» course for the convenience of their use in the process of educational work with students – future Environmental Designers.

Резюме. Стаття присвячена проблемі формування іншомовної професійної компетентності майбутніх дизайнерів середовища. Виконано аналіз відповідної науково-педагогічної літератури. Метою статті є аналіз моделювання професійно-орієнтованого ситуаційного навчання як педагогічної умови формування іншомовної професійної компетентності майбутніх дизайнерів навколишнього середовища. Доведено, доцільність використання вправ на індивідуальне та колективне вирішення широкого спектру питань у сфері концептуалізації, композиції, стилізації, формо- і кольоротворення, матеріалозабезпечення дизайн-об’єктів різного функціонального призначення з підготовкою засобів візуалізації і вербальної презентації іноземною мовою та ситуаційних завдань чітко вираженого комунікативного характеру на відпрацювання норм іншомовної комунікативної поведінки.
The modelling of professionally oriented situated learning as a pedagogical condition for forming foreign language professional competence of future environmental designers
Весь випуск: https://sites.google.com/uica.education/nayka/%D0%BD%D0%B0%D1%83%D0%BA%D0%BE%D0%B2%D1%96-%D0%B7%D0%B0%D0%BF%D0%B8%D1%81%D0%BA%D0%B8-16?authuser=0
Keywords: підготовка майбутніх бакалаврів; фахівець з дизайну середовища; іноземна мова професійного спрямування; іншомовна професійна компетентність дизайнера середовища; training of future bachelors; specialists in Environmental Design; foreign language for specific purposes; foreign language professional competence of an Environmental Designer